Citra Ibu Dalam Puisi “Pulang Ke Dapur Ibu” Karya Aan Mansyur Dan Lirik Lagu “Bertaut” Karya Nadin Amizah - Elpida Fathi Garwita; Assifa Atsna Hanifa (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to describe how the image of a mother is compared based on physical aspects, psychological aspects, and social aspects in poetry and song lyrics. The poem in question is "Pulang ke Dapur Ibu" by Aan Mansyur about how a mother becomes the safest and most comfortable place for a child to return to in the midst of the complexities of life that the child lives, while the song lyrics in question are "Bertaut" by Nadin Amizah about the closeness of a child to his mother in the context of childhood to adulthood. This study was conducted using qualitative methods, supported by data collection techniques in the form of observing and taking notes, as well as data analysis techniques in the form of qualitative analysis. The results of the study show that the image of a mother in the poem "Pulang ke Dapur Ibu" by Aan Mansyur shows: (1) physical aspects in the form of being old or old so that she cannot carry out daily activities as before; (2) psychological aspects in the form of always showing happiness in front of the child, hiding sadness and problems from the child; and giving full attention and affection to the child; and (3) social aspects in the form of carrying out the role of a parent, in the household, and in work. Meanwhile, the image of a mother in the lyrics of the song "Bertaut" by Nadin Amizah shows: (1) the physical aspect in the form of a strong and brave mother figure; (2) the psychological aspect in the form of how a mother becomes a figure who provides support and celebrates her child's success, the way she behaves which then builds attachment, and how a mother acts as a source of knowledge, answers, and experience for her child; and (3) the social aspect in the form of the mother's role as a parent.